MENINGKATKAN KETERAMPILAN BELAJAR MAHASISWA DENGAN MODUL BELAJAR MANDIRI - Cecep Kustandi, Suprayekti, Hirmana Wargahadibrata (Perspektif Ilmu Pendidikan, 2016)
Learning skill functions as the basic foundation to enable the students to attain good learning achievement and practice optimal self-actualization at their work places. However, in fact majority of the students have not possessed learning skills for effective remembering, planning learning schedule, effective note-taking, fast and effective reading. This research aims at producing self-study module to facilitate the students to improve their learning skill in higher education. The model applied in this research was Rowntree’s research and development. The research was conducted for 11 months as from Jan through November 2014 in The School, Education of State University of Jakarta.The research result showed the module was effective based on expert review, one to one evaluation, small group, and field trials. It could improve the students’ learning skill. The implication of this study is the module facilitates the students to learn independently and develop their learning skills so that they can achieve the expected graduate competence.